Fresh-state and mechanical properties of high-performance self-compacting concrete with recycled aggregates from the precast industry - Barroqueiro, Tiago (2020)
The urgent need to change the less positive impacts of the construction industry on the environment, and more specifically the production and use of concrete, is the main motivation for the research for more efficient and environmentally sustainable solutions. This paper presented the results of an experimental campaign whose ultimate goal was to produce high-performance self-compacting concrete (SCC) using recycled aggregates (RA) from the precast industry. The results of the fresh-state and mechanical properties tests performed on six concrete mixes (using RA from the precast industry) were presented. The first concrete mix is a reference mix using natural aggregates only (100% NA), and the remaining five mixes had various contents of fine (FRA) and coarse (CRA) recycled aggregates in concrete’s composition: (2) 25/25% (25% RA); (3) 50/50% (50% RA); (4) 100/100% (100% RA); (5) 0/100% (100% CRA); (6) 100/0% (100% FRA). The results showed that the high-performance concrete mixes with RA from the precast industry performed worse than the reference mix. However, taking into account all the mechanical properties studied, it can be concluded that RA from precast concrete elements are of very good quality and can be incorporated in the production of high-performance SCC. The potential demonstrated by the combined use of fine and coarse recycled aggregates was also emphasized. This type of work is expected to effectively contribute to raise awareness among the various players in the construction industry, particularly in the precast concrete industry, to the feasibility of using RA in significant quantities (notably coarse aggregates) and to the safety needed to assume structural functions, even for applications where high performance is required.